AN ANALYSIS OF SPEAKING LANGUAGE LEARNING STRATEGIES USED BY STUDENTS’ OF STKIP MUHAMMADIYAH MUARA BUNGO - Ridho Kurniawan; Yahfenel Evi Fussalam (Universitas Muhammadiyah Muara Bungo, 2018)
This research focus on an investigation students’ speaking language learning strategies were used by the second semester students’ of English Department STKIP Muhammadiyah Muara Bungo (STKIP-MB). The researcher analyzed speaking learning strategies components based on the Oxford’s theories included direct strategies such as memory strategies, cognitive strategies, compensation strategies, and indirect strategies such as metacognitive strategies, affective strategies, and social strategies. The method of this research was descriptive quantitative. The data of this research were analyzed by using two methods of data analysis. Quantitative data analysis was used to examine and interpreted data from speaking test and questionnaire. The data taken from observation, field note and interview were analyzed by using qualitative data analysis. The finding shows that (1)There are many speaking learning strategies used by the students of English Department STKI-MB. The students who used memory strategies is 54.7%, the students who used cognitive strategies is 50.3 %, the students who used compensation strategies is 62.3%, the students which used metacognitive strategies is 42.0%, The students who used affective strategies is 39.3% and the last, the students who used social strategies is 51.8%. (2) The most frequently strategy that used by students was compensation strategy 62.3%. This study indicated that the speaking learning strategies are possible to affect the assessment score of the students’ speaking quality.